A Systematic Overview Of Abdominal Aortic Aneurysm (AAA) - Laksono, Gerardo AK; Tahalele, Paul L (JOURNAL OF WIDYA MEDIKA JUNIOR, 2020)
An abdominal aortic aneurysm (AAA) is defined as an abnormal dilatation of the abdominal aorta more than 50% of its diameter. The aortic wall continues to weaken and become unable to hold the forces of the luminal blood pressure, resulting in progressive dilatation and rupture. The rupture of the aneurysm wall is influenced by several factors, such as the aneurysm size, expansion rate, continued smoking, and persistent hypertension. The AAA is a common degenerative condition with high mortality in older people. The AAA increases these last two decades. It is occurring in 7-8% of men at the age of over 65 years old. The disease prevalence is six times higher in men than in women. It is also increasing dramatically by the presence of the following factors: age older than 60 years old, smoking, hypertension, and ethnicity. Repair of large or symptomatic AAA by open surgery or endovascular is recommended, but not significant in the small aneurysm.